2000
DOI: 10.1046/j.1365-2265.2000.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweat secretion rates in growth hormone disorders

Abstract: We have demonstrated that longstanding GH hypersecretion in patients with acromegaly induces irreversible changes of sweat gland function, with persistently elevated SSR despite treatment and clinical cure. In GHD patients, SSR was reduced in males but not in females, which together with the established gender difference in normal controls emphasises the role of androgen deficiency as a cofactor for reduced sweating in hypopituitary patients. Sweat gland development seems to be more susceptible to lack of horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
(35 reference statements)
0
18
2
Order By: Relevance
“…In a previous study involving patients with AO-GHD of mean duration 8.6 years (range 2±27 years) since diagnosis, we found that SSR was similar to controls in female patients, but lower compared with controls in male patients. Eighteen months of GH replacement therapy did not effect SSR in either group (4). In the present study, only male patients were present in the untreated GHD group.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…In a previous study involving patients with AO-GHD of mean duration 8.6 years (range 2±27 years) since diagnosis, we found that SSR was similar to controls in female patients, but lower compared with controls in male patients. Eighteen months of GH replacement therapy did not effect SSR in either group (4). In the present study, only male patients were present in the untreated GHD group.…”
Section: Discussioncontrasting
confidence: 60%
“…The impact of the decreased sweating ability is also demonstrated by the fact that some patients with GHD are poikilothermic (13). Conversely, acromegaly is associated with excess sweating and increased SSR (4,8). The changes in GHD may be a result of atrophy of the eccrine sweat glands because of lack of stimulation of either GH or IGF-I, or both.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations